1992
DOI: 10.1088/0953-4075/25/17/020
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture and ionization in collisions of fast H+and He2+ions with magnesium atoms

Abstract: A crossed beam technique incorporating time-of-flight spectroscopy and coincidence counting of fast ion-slow ion and electron-slow ion collision products has been used to obtain individual cross sections for electron capture, transfer ionization and pure ionization in collisions involving Mg atoms. Processes involving Mgn+ formation for n between 1 and 4 have been considered for both 90-2000 keV amu-1 H+ impact and 43-500 keV amu-1 He2+ impact. The results extend available data to energies where, in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…The three-state close-coupling calculations (Olson and Liu 1979) for the H + -Mg system indicated that the capture cross sections to the n = 1 state with excitation of the resulting target ion dominates the electron capture at energies 50-10 000 eV. Although there exists reasonably good agreement between previous calculations (Morgan and Eriksen 1979a, Olson and Liu 1979, Garcia-Madroñal and Mo 1991 and experiments (Il'in et al 1965, Futch and Moses 1967, Berkner et al 1969, Morgan and Eriksen 1979a, DuBois et al 1985, DuBois 1986, Shah et al 1992, Cisneros et al 1996 for the total cross sections there has been very limited measurements and calculation of the partial capture cross sections. We have calculated total and partial capture cross sections in the energy range from 1 to 500 keV, showing the importance of capture into the excited states of hydrogen (n = 2) which have not been carefully considered in previous theoretical studies and for which there is limited experimental information.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…The three-state close-coupling calculations (Olson and Liu 1979) for the H + -Mg system indicated that the capture cross sections to the n = 1 state with excitation of the resulting target ion dominates the electron capture at energies 50-10 000 eV. Although there exists reasonably good agreement between previous calculations (Morgan and Eriksen 1979a, Olson and Liu 1979, Garcia-Madroñal and Mo 1991 and experiments (Il'in et al 1965, Futch and Moses 1967, Berkner et al 1969, Morgan and Eriksen 1979a, DuBois et al 1985, DuBois 1986, Shah et al 1992, Cisneros et al 1996 for the total cross sections there has been very limited measurements and calculation of the partial capture cross sections. We have calculated total and partial capture cross sections in the energy range from 1 to 500 keV, showing the importance of capture into the excited states of hydrogen (n = 2) which have not been carefully considered in previous theoretical studies and for which there is limited experimental information.…”
Section: Introductionmentioning
confidence: 61%
“…However, detailed studies of collisions involving Mg atoms have not been extensive both from the experimental and theoretical points of view. Total single-electron capture cross sections for H + impact on Mg have been previously measured by Il'in et al (1965) in the energy range 10-180 keV, by Futch and Moses (1967) from 4-50 keV, by Berkner et al (1969) from 5-70 keV, by Morgan and Eriksen (1979a) from 1-100 keV, by Cisneros et al (1996) from 1.0-5.0 keV, by DuBois and Toburen (1985) and DuBois (1986) from 2-100 keV, and by Shah et al (1992) from 90-500 keV. From a theoretical point of view, Mg atoms can be considered as a prototype of metals with two outer electrons.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our measured relative cross sections were normalized to our previously measured cross sections (Patton et al 1996) for ionization of Ga by electron impact. This procedure, which has been described in detail previously (Shah et al 1992), involved the substitution of a pulsed primary ion beam by a pulsed beam of electrons while the target-beam conditions remained unchanged.…”
Section: Experimental Approachmentioning
confidence: 99%
“…In this note we describe an oven source of simple and compact design which has been used in crossed beam experiments in this laboratory (cf Shah et al 1992Shah et al , 1993 with both electron and ion beams. Metallic species have included gallium, magnesium, copper and iron with melting points ranging from 30 • C to 1535 • C.…”
Section: Introductionmentioning
confidence: 99%